2010
DOI: 10.1016/j.neuint.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide potentiation of miniature spontaneous excitatory synaptic transmission is mediated via IP3 pathway

Abstract: Although arachidonoyl ethanolamide (AEA or anandamide) is the first identified endocannabinoid, its roles in synaptic signaling and neuronal survival are still controversial. Here we report that AEA induced a dose-dependent elevation of the frequency of miniature excitatory postsynaptic currents (mEPSCs) in mouse hippocampal neurons in culture. This potentiation was not blocked by SR141716 or AM251, selective cannabinoid receptor antagonists), indicating that the AEA elevation of mEPSCs is not mediated via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Huang et al showed the reduction of synaptic transmission on corticostriatal brain slices by application of 20-μM AEA (Huang et al, 2001). Lower AEA concentrations instead, seem to potentiate synaptic transmission as shown by Sang et al (2010) on primary hippocampal neuron cultures. In pharmacologically relevant concentrations, endocannabinoids are also known to modulate functional properties of voltage-gated ion channels including Na + and K + channels (Oz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al showed the reduction of synaptic transmission on corticostriatal brain slices by application of 20-μM AEA (Huang et al, 2001). Lower AEA concentrations instead, seem to potentiate synaptic transmission as shown by Sang et al (2010) on primary hippocampal neuron cultures. In pharmacologically relevant concentrations, endocannabinoids are also known to modulate functional properties of voltage-gated ion channels including Na + and K + channels (Oz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Primary hippocampal neurons from rat (Sprague Dawley) embryos (E18) or P0 were cultured as described previously (Sang et al, 2005; 2007; Zhang & Chen, 2008, Sang et al, 2010), according to the guidelines approved by the Institutional Animal Care and Use Committee of of Louisiana State University Health Sciences Center in New Orleans. Briefly, after suffocation with carbon dioxide, unconscious animals were decapitated.…”
Section: Methodsmentioning
confidence: 99%
“…A major synthetic enzyme for anandamide, N-acylphosphatidylethanolamine-specific phospholipase D (NAPE-PLD) [120] is found in some glutamatergic nerve terminals, but not postsynaptic pyramidal cell bodies [121][122], arguing against its being the source of anandamide in either TRPV1-mediated LTD [119] [54], or CB1R-mediated homeostatic plasticity [53]. The association of NAPE-PLD with intracellular, perhaps Ca 2+ -containing cisternae [121], might explain the recent finding that anandamide can induce quantal glutamate release via a CB1R- and TRPV1-independent mechanism [123]. Working out the biosynthetic mechanisms [124] of anandamide production and its modes of action are pressing tasks for the future.…”
Section: Endocannabinoids As Retrograde Messengers For Synaptic Plastmentioning
confidence: 99%